Monoacylglycerol lipase inhibitor JZL184 reduces neuroinflammatory response in APdE9 mice and in adult mouse glial cells - Pihlaja R; Takkinen J; Eskola O; Vasara J; Lopez-Picon FR; Haaparanta-Solin M; Rinne JO (BIOMED CENTRAL LTD, 2022)
Conclusions: JZL184 decreased the proinflammatory reactions of microglia and reduced the total A beta burden and its precursors in the APdE9 mouse model. It also reduced the proinflammatory responses of microglia and astrocytes isolated from adult mice.